Hepatitis C Prevalence and Validation of a Clinical Prediction Score for Targeted Screening among People Living with HIV in Ghana - Torpey, K.; Ogyiri, L.; Cuylaerts, V.; Agyeman, S.; Agyei-Nkansah, A.; Buyze, J.; Commey, J.O.; Lynen, L.; De Weggheleire, A. (SAGE, 2021)
WHO recommends hepatitis C (HCV) screening for all people living with HIV (PLHIV). Yet, HCV coinfection was shown to be rare in some Sub-Saharan HIV cohorts, and targeted testing was suggested more efficient for such settings. We studied HCV prevalence among Ghanaian PLHIV, and assessed the external validity of a score to guide targeted testing. This score was initially derived from a Cambodian HIV cohort, and uses as predictors: age, household member/partner with liver disease, diabetes, generalized pruritus, AST, platelets, and AST-to-platelet ratio index. We enrolled 4,023 PLHIV, most from Greater Accra and Central regions, 28.4% were male, median age was 47 years, and high-risk behavior was reported to be rare. HCV seroprevalence was 0.57%, and HCV-RNA was detectable in 0.5%. Sequencing revealed genotype 1(b) and 2(q/r) infections. The discriminatory performance of the score was suboptimal in the Ghanaian setting. The area under the curve was 0.69 (95% CI 0.59-0.79). HCV coinfection prevalence was very low in this Ghanaian PLHIV cohort with reported low-risk of onward transmission. To avoid the cost of screening all PLHIV in similar cohorts in resource-constrained settings, further research to develop better tools/scores to guide targeted HCV testing is needed.
Research Article
Keywords: hepatitis C prevalence; HIV; HCV/HIV coinfection; clinical prediction score; targeted screening; Ghana